Temporal dynamics of a subtropical urban forest in San Juan, Puerto Rico, 2001-2010 (2013)
Several studies report urban tree growth and mortality rates as well as species composition, structural dynamics, and other characteristics of urban forests in mostly temperate, inland urban areas. Temporal dynamics of urban forests in subtropical and tropical forest regions are, until now, little explored and represent a new and important direction for study and management of these ecosystems. This study used permanent plots and statistical models incorporating tree and plot-level covariates to analyze mortality, in-growth, diameter growth, and species composition, as well the socioeconomic and urban morphology factors driving change in San Juan, Puerto Rico's subtropical coastal island urban forests over a nine year period. A total of 87 plots contained 482 trees in 2001 and 749 trees in 2010. Between 2001 and 2010 average tree densities increased, and average annual mortality rates were nearly 30%. Mortality was lower for larger, open-grown, non-leguminous trees and in higher income neighborhoods, but higher for street trees and larger population areas. The most widespread tree was invasive Spathodea campanulata, but overall, average mortality was higher for invasive than non-invasive tree species. In-growth of invasive species increased with human population, while higher tree densities corresponded with increased in-growth of native species. Overall mean diameter growth rate was 0.98 cm/yr, but remnant forest patch growth rates were 0.35 cm/yr. Higher diameter growth rates were associated with larger human populations, amounts of duff/mulch cover, and open-grown conditions. This study adds new insights to broaden our understanding of these emergent ecosystems in the Caribbean region.